Implementation of Chemistry Teaching Material Integrated with Spiritual Values Using the Problem Based Learning Model to Improve Learning Outcomes Reviewed from Learning Motivation - Shelly Aulia; Ayi Darmana (Jurnal Pendidikan dan Pembelajaran Kimia, 2025)
Implementation of Chemistry Teaching Material Integrated with Spiritual Values ​​Using the Problem Based Learning Model to Improve Student Learning Outcomes Reviewed from Learning Motivation. This study aims to investigate the significant influence of chemistry teaching materials based on spiritual values on student learning outcomes, reviewed from student learning motivation using the Problem-Based Learning (PBL) model. A quantitative approach with a quasi-experimental design was employed. The sample consisted of two randomly selected groups of Grade XI students: the experimental group (Class XI-1), which received instruction using spiritual value-based materials integrated with the PBL model, and the control group (Class XI-3), which used conventional materials. Data were collected through posttests to assess learning outcomes and questionnaires to measure learning motivation. Data analysis included normality, homogeneity tests, and a two-way ANOVA. The results showed that the experimental group achieved a higher average posttest score (77.0) compared to the control group (71.89), indicating improved learning outcomes. The two-way ANOVA revealed a significant effect of learning motivation on learning outcomes (p = 0.000 < 0.05), as well as a significant interaction between spiritual value-based teaching materials and motivation (p = 0.03 < 0.05). These findings suggest that the integration of spiritual values in chemistry teaching materials, when combined with the PBL model, positively and significantly enhances student learning outcomes, especially when students are highly motivated to learn.